Optimal discharge locations to refill hydric reservoirs with reused water - application to the jaunay lake case study - Crespo, María; Orsoni, Julien; Bortoli, Jérôme; Rapaport, Alain; Rousseau, Antoine; Jauzein, Vincent (Revue des sciences de l’eau / Journal of Water Science, 2018)
In this work, we study optimal strategies of wastewater reuse for refilling Jaunay Lake (a water reservoir located on the French western coast) which shows an alarming volume reduction due to the human water intake. To grasp the multiple issues to ascertain the appropriate location for the reused water discharge, mathematical modelling is particularly adapted for testing different conditions (physical, meteorological) and optimizing the system to achieve targets (maximum allowable concentration of pollutant for drinking water and recreational uses). We focus on modelling the distribution of a generic pollutant in the reservoir, which is expected to vary with time and space. The model assumes that the reservoir volume stays constant (because the flow rates at the refilling and removal points are considered to be quasi-identical), the density of the pollutant is smaller than that of the reservoir water (so that the pollutant remains at the top level of the water column) and its dynamics is influenced by two main effects: wind and water currents. The model accounts for the reservoir geometry, the operating conditions of the transfer pipes (input and output) and real data regarding chronicles of wind velocity and river flow. Then, we tackle a multi-optimization problem which aims to find optimal refilling locations which reduce the pollutant concentration at two strategic regions of the reservoir. A Pareto front is presented as a decision-tool to choose the optimal strategy according to different water quality criteria.